Al-Isyārāt Al-Ilmiyah ‘Alā Al-Hūt Wa Al-Yaqthïn Fi Qishah Yunus -‘Alaihi As-Salām- ‘Inda Zaghlul Rāghib Muhammad An-Najār: الإشارة العلمية علي الحوت واليقطين في قصة يونس- عليه السلام- عند زغلول راغب محمد النجار - Maisurah, Rezki Kaulan; Nasution, Alhafidh; Septrianto, Wahyu; Herisnawan, Diky (Sekolah Tinggi Ilmu Al-Qur'an (STIQ) ZAD, 2023)
So in this case the researchers want to reveal the side of I'jaz 'ilmi contained in the kauniyah verse in the story of Yunus AS, according to Zaghlul an-Najjar, al-hut, and yaqthin. Researchers try to find out the side of I'jaz ilmi with scientific thematic studies and studied through literature research, the methods used are descriptive methods and analysis. Zaghlul proved the existence of I'jaz ilmi in the story of Yunus AS with the proposition that there is a match between his story in the Qur'an and the results of recent modern discoveries, namely by identifying the meaning of al-hut in the story of Yunus as a type of blue whale, and the yaqthin fruit (pumpkin) that has cured him from illness is considered important and useful such as being able to guard against cancer and digestion. And he concluded it all as proof of the truth of the Qur'an and as a miracle of the Prophet Muhammad (peace be upon him) and the revelation that came down from Allah SWT.